PERSPECTIVES OF USING OF HIGH-SPEED STEELS FOR PRODUCTION OF CAST METAL-CUTTING INSTRUMENT. THE PECULIARITIES OF STRUCTURE AND CHARACTERISTICS OF CAST AND DEFORMED STEELS - A. S. Chaus; M. Legerska; F. I. Rudnitskij; A. N. Konstantjuk; K. F. Rudnitskij (Литьë и металлургия)
In the article there are examined the different ways of improvement of the structure and properties of the high-speed steels, intended for production of the cast metal-cutting instrument. It is shown, that effective methods of improving of impact elasticity of the cast high-speed steel are modification and accelerated cooling of melt at primary crystallization, electroslag remelting with using of magnetic field, and also using of steels with decreased structure dissimilarity.